Multilevel Analysis on the Association of Job Satisfaction and Organization Commitment with Performance of Family Planning Counsellor in Yogyakarta - Ikhtiarisca Olifia Mufidatun; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Performance is an important thing in an organization's efforts to achieve the goals. To evaluate employees objectively, a supervisor must be able to measure their performance level. There are many job characteristics that employees consider, but a group of job characteristics tends to be collectively evaluated in the same way. This study aimed to analyze the effect of job satisfaction and organizational commitment on the employee performance of the Family Planning Counselors in YogyakartaSubjects and Method: This study used a cross-sectional study. This study was conducted in the office of Family Planning Field Officer (PKB), Yogyakarta, Central Java, from January to February, 2020. There were 200 employees as the sample of this study. The sample was collected using simple random sampling. The dependent variable was the performance of PKB employees. The independent variables were job satisfaction and organizational commitment. The data were collected using questionnaires. The data were analyzed using multilevel analysis with Stata 13.Results: The performance of PKB employess increased with poor good job satisfaction (b=2.36; 95%CI=1.49 to 3.22; p<0.001) and good organizational commitment (b=1.68; 95%CI=0.89 to 2.47; p<0.001). PKB office had a contextual effect on employee performance with ICC=10.75%.Conclusion: Job performance is affected by job satisfaction and organizational commitment. PKB Office has a strong contextual effect on job performance.Keywords: employee performance, job satisfaction, organizational commitmentCorrespondence: Ikhtiarisca Olifia Mufidatun. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, 57126, Surakarta, Central Java. Email: riscaolifia@gmail.com. Mobile: +6282220030006Journal of Health Policy and Management (2020), 05(03): 197-203https://doi.org/10.26911/thejhpm.2020.05.03.05